Subsequent Fertility in Women Treated for Caesarean Scar Pregnancy With Hysteroscopy: A 5-Year Follow-Up Descriptive Study in a Tertiary Hospital - Sun, Xinyi; Liu, Yang; Tang, Yunhui; Yu, Hongying; Zhao, Min; Chen, Qi (Frontiers in Endocrinology, 2021)
Objective: The outcomes of subsequent pregnancies and fertility in women with a history of caesarean scar pregnancy have not been well described. In this study, we followed up 149 women with a history of caesarean scar pregnancy and analysed the effect on their fertility. Methods: 149 women with a history of caesarean scar pregnancy were followed up for five years. Of them, 53 women had unprotected sexual intercourse attempting to become pregnant again. Data including clinical parameters and treatment options at the time of diagnosis of caesarean scar pregnancy, and the outcomes in subsequent pregnancy were collected. In addition, a questionnaire about the menstrual cycle after treatment was voluntarily completed by these women. Results: Of the 53 women, 46 (84%) women had a subsequent pregnancy, while 7 (14%) women did not. There was no association between the clinical parameters in previous caesarean scar pregnancy or treatment and future fertility. From the questionnaire, there was no difference seen in the length of the menstrual cycle and menses between the two groups. However, a higher number of women with light menstrual bleeding was seen in women without a subsequent pregnancy (67%), compared with women who did (28%). In addition, 6 women (13%) who had a subsequent pregnancy experienced foetus death in the first trimester. Conclusion: We reported that 14% of women with a history of cesarean scar pregnancy did not have a subsequent pregnancy, after unprotected sexual intercourse for more than two years. Light menstrual bleeding after treatment may be associated with this adverse effect. Our findings need to be further investigated with a large sample size.